Conversion of coal mine drainage ochre to water treatment reagent: Production, characterisation and application for P and Zn removal. (1st September 2015) - Sapsford, Devin; Santonastaso, Marco; Thorn, Peter; Kershaw, Steven
Abstract: Coal mine drainage ochre is a ferruginous precipitate that forms from mine water in impacted watercourses and during treatment. With thousands of tonnes per annum of such ochre arising from mine water treatment in the UK alone, management of these wastes is a substantive issue. This paper demonstrates that the ochre from both active and passive treatment of coal mine drainage can be transformed into an effective water treatment reagent by simple acid dissolution and that the reagent can be used for the removal of dissolved phosphorous from municipal wastewater and zinc from non-coal mine waters. Ochre is readily soluble in H2 SO4 and HCl. Ochre is more soluble in HCl with solubilities of up to 100 g/L in 20% (w/w) HCl and 68 g/L in 10% (w/w) H2 SO4 . For four of the eight tested ochres solubility decreased in higher concentrations of H2 SO4 . Ochre compositional data demonstrate that the coal mine ochres tested are relatively free from problematic levels of elements seen by other authors from acid mine drainage-derived ochre. Comparison to British Standards for use of iron-based coagulants in drinking water treatment was used as an indicator of the acceptability of use of the ochre-derived reagents in terms of potentially problematic elements. The ochre-derived reagents were found to meet the 'Grade 3' specification, except for arsenic. Thus, for application in municipal wastewater and mine water treatment additional processing may not be required. There was little observed compositional difference between solutions prepared using H2 SO4 or HCl. Ochre-derived reagents showed applicability for the removal of P and Zn with removals of up to 99% and 97% respectively measured for final pH 7–8, likely due to sorption/coprecipitation. Furthermore, the results demonstrate that applying a Fe dose in the form of liquid reagent leads to a better Fe:P and Fe:Zn removal ratio compared to ochre-based sorption media tested in the literature. Highlights: Mine water treatment ochre was converted to reagent capable of removing P and Zn. Ochre-derived reagents resulted in a higher removal compared to using ochre solids. Ochre solubilities of up to 100 g/L were found in 20% (w/w) HCl. Ochres were relatively free from problematic elements.